Prinsip Interkoneksi Informasi Dalam Penanganan Bencana Banjir - Dicky Rezady Munaf (Jurnal Sosioteknologi, 2007)
Due to its geographical characteristics, the natural disasters in Indonesia are inevitable. However, the problem can be anticipated by emphirical experience and traditional knowledge. This paper discusses the interconnection of the two factors so that it will generate the early waning culture in Indonesia.